Towards a New Visual Query Language for GIS - Haraty, Ramzi (2006)
In recent years, many non-expert user applications have been developed to query Geographic Information Systems (GIS) that are used to browse and view data about space and time thus naming them spatio-temporal databases. Our research aims at designing and developing an International Visual Query Language (IVQL) that allows users to query databases based on their location. The databases are installed on a GIS server computer. The queries are sent to the server from a mobile phone through the Short Messages System (SMS). With the emerging Globalization of user interfaces, IVQL is meant to have a global and international user interface that could be understood by all users worldwide who are from different countries with different cultures and languages. We propose a user interface consisting of smiley icons that are used to represent and build an international query language. Smiley icons enable the users to access data and build queries easily and in a user-friendly way. The visual query language, its user interface and its model are explained. The query formulation is illustrated using a sample GIS system for tourists. IVQL can be applied to fields such as Management Information Systems and tourism. We then conclude about our future work.